2017
DOI: 10.1007/8904_2017_3
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Hydroxybutyrate (GHB) Content in Hair Samples Correlates Negatively with Age in Succinic Semialdehyde Dehydrogenase Deficiency

Abstract: Gamma-hydroxybutyrate (GHB) is a drug of abuse, an approved therapeutic for narcolepsy, an agent employed for facilitation of sexual assault, as well as a biomarker of succinic semialdehyde dehydrogenase deficiency (SSADHD). Our laboratory seeks to identify surrogate biomarkers in SSADHD that can shed light on the developmental course of this neurometabolic disease. Since GHB may be quantified in hair as a potential surrogate to identify victims of drug-related assault, we have opted to examine its level in SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…1 Recent longitudinal studies have demonstrated changes in GABA and GHB levels with age, with highest levels seen in the first years of life. 2,3 Clinical presentation is typically hypotonia and developmental delay. Nonprogressive ataxia, hyporeflexia, behavioral dysregulation, obsessive-compulsive disorder, anxiety disorder, and attention-deficit/hyperactivity disorder are additional signs and symptoms with high prevalence.…”
mentioning
confidence: 99%
“…1 Recent longitudinal studies have demonstrated changes in GABA and GHB levels with age, with highest levels seen in the first years of life. 2,3 Clinical presentation is typically hypotonia and developmental delay. Nonprogressive ataxia, hyporeflexia, behavioral dysregulation, obsessive-compulsive disorder, anxiety disorder, and attention-deficit/hyperactivity disorder are additional signs and symptoms with high prevalence.…”
mentioning
confidence: 99%
“…47,48 An age-dependent decrease in GABA and GHB levels toward more normal values follows. 49,50 This decrease in GABA and GHB levels, paired with downregulation of GABA-A and GABA-B receptors, 10,48 may explain the evolving phenotype seen in human subjects, who show more tendency toward compulsive behavior, sleep disturbance, and seizures with age. 5 The outcome measures we used, the Adaptive Behavior Assessment Scale and transcranial magnetic stimulation parameters, may not have been sensitive enough to show therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…GHB can be clinically assessed in whole blood, plasma, or dried blood spots 3,4 ; however, a negative correlation with age has been reported for GHB levels in dried blood spots, wherein the GHB concentrations for some patients previously diagnosed with SSADHD, when assessed at older ages, were below the threshold determined for newborn detection. 3,5 -7 These findings indicate that some individuals, when assessed at older ages, may be missed with current biomarker cutoffs, increasing the need to better understand variant pathogenicity. 3,5,6…”
mentioning
confidence: 99%
“…3,5 -7 These findings indicate that some individuals, when assessed at older ages, may be missed with current biomarker cutoffs, increasing the need to better understand variant pathogenicity. 3,5,6…”
mentioning
confidence: 99%